2020
DOI: 10.3389/fendo.2020.00052
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Glomerular Filtration Rates Calculated by New and Old Equations in Children and Adolescents With Type 1 Diabetes—What to Do With the Results?

Abstract: Background: To apply and evaluate various equations for estimated glomerular filtration rates (eGFR) in a large paediatric type 1 diabetes population and compare the eGFR values with urinary creatinine clearances (UCC) in a subset of patients.Methods: Six eGFR formulae applicable for children and adolescents were used for calculation of eGFR values in 36,782 children/adolescents with type 1 diabetes. Via regression models, factors influencing eGFR values were identified. eGFR values were compared with measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
7
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
8
7
1
1
Order By: Relevance
“…In line with former studies in healthy or T1D adolescents [13][14][15] , also in our study different pediatric formulae returned diverse mean eGFR values. Five out of six equations indicated sex differences in mean eGFR -but neither consistently regarding whether mean eGFR was higher in males or females, nor completely matching the sex differences reported by Boettcher et al for a large group of children and adolescents with T1D 15 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with former studies in healthy or T1D adolescents [13][14][15] , also in our study different pediatric formulae returned diverse mean eGFR values. Five out of six equations indicated sex differences in mean eGFR -but neither consistently regarding whether mean eGFR was higher in males or females, nor completely matching the sex differences reported by Boettcher et al for a large group of children and adolescents with T1D 15 .…”
Section: Discussionsupporting
confidence: 92%
“…In line with former studies in healthy or T1D adolescents [13][14][15] , also in our study different pediatric formulae returned diverse mean eGFR values. Five out of six equations indicated sex differences in mean eGFR -but neither consistently regarding whether mean eGFR was higher in males or females, nor completely matching the sex differences reported by Boettcher et al for a large group of children and adolescents with T1D 15 . The difference between the highest and the lowest mean eGFR in our study was similar to that reported for 12-to-17year-old US adolescents (43 mL/min/1.73 m 2 ) 14 but higher than the difference of about 16 mL/min/1.73 m 2 in males, and 20 mL/min/1.73 m 2 in females observed in 1-to-<18-year-old T1D patients 15 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using serum creatinine alone is unreliable because its level is dependent on a number of factors that have nothing to do with a patient’s renal function. Instead an estimated glomerular filtration rate (eGFR) derived from prediction equations has been suggested as an important measure for assessing renal function [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%